ISPO Policy on Palm Oil Industry and Biodiesel Development in North Aceh - Jamaluddin; Faisal; Sari, Elidar; Jumadiah (Magister of Law, Faculty of Law, University of Mataram, 2023)
The total area of oil palm plantations in Aceh Utara Regency is 33,781.64 hectares, managed and operated by 11 oil palm plantation companies. In accordance with the Regulation of the Minister of Agriculture Number 11/Permentan/Ot.140/3/2015 regarding the Indonesian Sustainable Palm Oil Certification System (ISPO), the Government of Aceh Utara Regency has formulated a vision for the palm oil industry within its jurisdiction. This vision is centered around sustainability and its influence on the growth of the biodiesel sector in Aceh Utara Regency. To achieve this, the government encourages the palm oil industry to adopt ISPO certification. This research aims to analyze and describe the challenges, roles, and initiatives undertaken by the Government in Aceh Utara Regency to promote ISPO certification within the palm oil industry. The research employs an empirical juridical approach, encompassing the identification of research subjects, a statutory analysis, and horizontal and vertical synchronization methodologies to address the implementation of ISPO certification. The results of study reveal that the Government of Aceh Utara Regency has actively motivated palm oil plantation entrepreneurs to swiftly pursue ISPO certification. The government has established a dedicated team and allocated funds to expedite the implementation of ISPO.